Numerical Simulation of Debris Flows of the Catastrophic Event of February 2019 in Mirave – Peru - Del Savio, Alexandre Almeida (2019)
Debris flows are geophysical phenomena, caused by torrential rain, which occur in mountainous areas, characterized by the detachment of slope and riverbed materials and their consequent dislodge through watersheds and streams. Debris flows usually carry sludge, water and rocks, and can destroy everything in their path. On February 8th, 2019, an event of this type occurred and destroyed Mirave’s community in Peru, which was located in the areas of transport and deposition of debris flows. This research presents the modeling and numerical simulation to reproduce the transport and deposition processes of the debris flow that occurred in Mirave. The initiation process of the debris flow in streams was represented by hydrographs obtained from the estimated rain runoff volumes and solid materials found at each evaluated micro watershed. The numerical simulation results show acceptable results in terms of reproduction of the extension of the affectation and deposition areas of solids related to the studied debris flow. The resulting velocity field shows an adequate representation of the erosion zones observed in the area. The model used for evaluating the disaster risk by debris flows can predict and delimit, with acceptable accuracy, the potentially dangerous areas for a mudslide event. The application of the proposed methodology for assessing the disaster risk due to debris flows at watersheds and streams is useful to understand the extent of debris flow affectation during extreme weather events, as well as to develop emergency plans, and to formulate disaster management policies in Peru or in other countries with similar conditions.